2022
DOI: 10.1177/10600280221117156
|View full text |Cite
|
Sign up to set email alerts
|

Abrupt Discontinuation Versus Taper of Hydrocortisone in Patients With Septic Shock

Abstract: Background: Although not mentioned in the most recent guidelines, the 2016 Surviving Sepsis Campaign guidelines recommend to taper corticosteroids once vasopressors are no longer needed; however, at the time of publication, there were no studies comparing taper versus abrupt discontinuation of corticosteroids. Objectives: The purpose of this study was to further evaluate the impact of abrupt versus taper discontinuation of corticosteroids in septic shock. Methods: This was a retrospective cohort study that inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…A recent retrospective study showed that abrupt discontinuation of corticosteroids was associated with a lower likelihood of vasopressor reinitiation when compared with taper discontinuation. 51 In the event of shock recrudescence, the decision to reinstitute hydrocortisone should be tailored to the specific clinical circumstances. Our recommendations regarding corticosteroid administration in various systemic inflammatory processes are summarized in Table 2.…”
Section: Laboratory Testingmentioning
confidence: 99%
“…A recent retrospective study showed that abrupt discontinuation of corticosteroids was associated with a lower likelihood of vasopressor reinitiation when compared with taper discontinuation. 51 In the event of shock recrudescence, the decision to reinstitute hydrocortisone should be tailored to the specific clinical circumstances. Our recommendations regarding corticosteroid administration in various systemic inflammatory processes are summarized in Table 2.…”
Section: Laboratory Testingmentioning
confidence: 99%